Does hair curl variation influence the efficacy of scalp cooling in the prevention of chemotherapy-induced alopecia in breast cancer patients? A randomized controlled pilot study - Obuseng, Odirile (Division of Radiology, 2022)
Background: Chemotherapy-induced alopecia (CIA) is a common side-effect of breast cancer treatment. Scalp cooling is reported to reduce CIA; however, it is unknown whether the efficacy is influenced by hair curvature. Methods: This 20-month randomized controlled trial recruited females, (18-65 years) with breast cancer to receive chemotherapy (Adriamycin or Epirubicin and Cyclophosphamide followed by Paclitaxel) with or without scalp cooling. The main outcomes were percentage alopecia (Severity ALopecia Tool scored by 3 dermatologists) in straight versus curly hair and treatment retention rates. Results: Forty-eight patients (24 per group) were randomized; 4 in each group withdrew before study visit1 and photographs of 3 in the cooling group could not be found for severity assessment. Thus 77% constituted the intention to treat population (17 cooling versus 20 control). Agreement on alopecia severity was good overall (ICC=0,94; 95% CI: 0.85 - 0.97) and at 6 of 7 time points. Overall, cooling significantly reduced CIA, relative to no cooling (58.15 ± 28.46 versus 37.29 ± 20.52; p:0.0167), however, percentage alopecia was cosmetically significant. There was no difference in CIA between cooling participants with straight (8) versus curly hair (9), (p:0.0740). The number of patients completing the various cycles of chemotherapy, declined from 77.1% at cycle 1 to 18.8% at cycle 7 for the whole study; from 100% each to 17.6% and 30% for cooling and control groups, respectively (p:0.451). Conclusions: This small study suggests that hair curvature has no significant impact on the efficacy of scalp cooling to reduce CIA, however this requires confirmation.